2004
DOI: 10.1002/cpe.755
|View full text |Cite
|
Sign up to set email alerts
|

Towards a more realistic comparative analysis of multicomputer networks

Abstract: SUMMARYSeveral studies have examined the relative performance merits of the torus and hypercube taking into account the channel bandwidth constraints imposed by implementation technology. While the torus has been shown to outperform the hypercube under the constant wiring density constraint, the opposite conclusion has been reached when the constant pin-out constraint is considered. However, these studies have assumed a pure uniform traffic pattern and deterministic routing. The 'uniform traffic' assumption is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2006
2006
2007
2007

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
0
6
2
Order By: Relevance
“…In this study we would rather focus on the unidirectional versions of these networks in order to contrast our results with those reached in previous similar studies [1,3,7,11,12,13].…”
Section: Introductioncontrasting
confidence: 59%
See 4 more Smart Citations
“…In this study we would rather focus on the unidirectional versions of these networks in order to contrast our results with those reached in previous similar studies [1,3,7,11,12,13].…”
Section: Introductioncontrasting
confidence: 59%
“…2D torus outperforms the hypercube). On the other hand, when the pin-out constraint is imposed, the study in [12] has concluded that for small, moderate, and large networks, the topology exhibiting the best relative performance is, respectively, the hypercube, the 2D torus, and the 3D torus.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations